2016
DOI: 10.1200/jco.2015.65.4194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of Relapse in Classical Hodgkin Lymphoma at Event-Free Survival Time Points and Survival Comparison With the General Population in British Columbia

Abstract: Patients with cHL who are event free at 2 years have an excellent outcome regardless of baseline prognostic factors. All patients with cHL had an enduring increased risk of death compared with the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 25 publications
6
40
1
Order By: Relevance
“…Accumulating data have indicated that treatment failure or disease progression within 24 months after diagnosis is associated with survival in several lymphoma subtypes . In a study of diffuse large B‐cell lymphoma, the OS of patients who achieved event‐free survival at 24 months (EFS24) was comparable to the expected survival in the general population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating data have indicated that treatment failure or disease progression within 24 months after diagnosis is associated with survival in several lymphoma subtypes . In a study of diffuse large B‐cell lymphoma, the OS of patients who achieved event‐free survival at 24 months (EFS24) was comparable to the expected survival in the general population .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of diffuse large B‐cell lymphoma, the OS of patients who achieved event‐free survival at 24 months (EFS24) was comparable to the expected survival in the general population . In a study of classical Hodgkin lymphoma, patients who achieved EFS24 had an excellent outcome regardless of baseline prognostic factors . In a study of FL, EFS24 was associated with a short OS in patients who received rituximab and CHOP as first‐line therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased pretest likelihood of relapse in patients with high-risk features, Hapgood et al have recently described the outcomes for HL patients treated in British Columbia, in which the risk of relapse for patients with HL who are event-free at 2 years is only 5.6%, and this risk is not significantly impacted by pretreatment risk factors. 26 Future prospective studies are needed to determine whether surveillance imaging might provide benefits in highly selected populations.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…[4][5][6] In multisystemic, severe forms of this disease, targeted treatments with the BRAF inhibitors, vemurafenib and dabrafenib, have been efficiently used in BRAF-mutated patients. [7][8][9] In wild-type (WT) BRAF patients, cobimetinib, a MEK inhibitor, has also been used with success.…”
Section: V600ementioning
confidence: 99%
“…[1][2][3][4][5][6] However, treatment of patients with advanced-stage disease with optimal chemotherapy, such as doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD), fails to cure as many as 15% to 25% of patients, necessitating secondary intensified treatment, which incurs major toxicity and is only successful in ;50% of patients. 1,7,8 Genuine improvement in these outcomes will require identification of novel effective agents that can be integrated with standard chemotherapy during primary treatment.…”
mentioning
confidence: 99%